2007
DOI: 10.1093/hmg/ddm359
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of the genetic variants of interferon regulatory factor 5 (IRF5) reveals a novel 5 bp length polymorphism as strong risk factor for systemic lupus erythematosus

Abstract: We analyzed a comprehensive set of single-nucleotide polymorphisms (SNPs) and length polymorphisms in the interferon regulatory factor 5 (IRF5) gene for their association with the autoimmune disease systemic lupus erythematosus (SLE) in 485 Swedish patients and 563 controls. We found 16 SNPs and two length polymorphisms that display association with SLE (P < 0.0005, OR > 1.4). Using a Bayesian model selection and averaging approach we identified parsimonious models with exactly two variants of IRF5 that are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
198
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(223 citation statements)
references
References 37 publications
16
198
1
Order By: Relevance
“…These three polymorphisms were selected for the study on primary SS based on our results from comprehensive association studies of IRF5 and STAT4, in which these polymorphisms account for most of the association signals with SLE. 13,16 Table 2 presents the results for the association between the three polymorphisms and primary SS obtained in this study in the cohorts from Sweden and Norway. It is notable that there was a slight difference in the risk allele frequencies for the IRF5 polymorphisms between Despite the low number of individuals in the Norwegian cohort, the CGGGG indel was significantly associated with primary SS and the IRF5 SNP rs10488631 showed a suggestive association with primary SS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These three polymorphisms were selected for the study on primary SS based on our results from comprehensive association studies of IRF5 and STAT4, in which these polymorphisms account for most of the association signals with SLE. 13,16 Table 2 presents the results for the association between the three polymorphisms and primary SS obtained in this study in the cohorts from Sweden and Norway. It is notable that there was a slight difference in the risk allele frequencies for the IRF5 polymorphisms between Despite the low number of individuals in the Norwegian cohort, the CGGGG indel was significantly associated with primary SS and the IRF5 SNP rs10488631 showed a suggestive association with primary SS.…”
Section: Resultsmentioning
confidence: 99%
“…Both the SNP rs2004640 and the CGGGG indel are associated with SLE, and in a recent study we have shown that the CGGGG indel alone accounts for all the association signals from multiple linked SNPs in the 5 0 region, including the SNP rs2004640. 13 However, the current association data available for IRF5 in primary SS do not exclude the possibility that there could be differences between the association patterns in SLE and primary SS if a more comprehensive set of markers would be analyzed in a large set of primary SS samples. The longer (4 Â CGGGG) risk allele of the CGGGG indel, which is located 64 bp upstream of the alternative exon 1a of IRF5, creates an additional binding site for the transcription factor SP1.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…9 Interferon regulatory factor-5 (IRF5), a transcription factor, regulates the expression of IFN-a genes, 10,11 thus making it a good candidate gene for SLE susceptibility. Recent publications have reported a significant association between single nucleotide polymorphisms (SNPs) and haplotypes of IRF5 and SLE, both in familyand population-based studies of patients from multiple ethnicities [12][13][14][15][16][17][18][19][20][21] (including meta-analyses) 16 ; however, these studies have not examined African Americans.…”
Section: Introductionmentioning
confidence: 99%